1999
DOI: 10.1002/(sici)1097-0282(1999)51:2<145::aid-bip4>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Peptides and proteins in neurodegenerative disease: Helix propensity of a polypeptide containing helix 1 of the mouse prion protein studied by NMR and CD spectroscopy

Abstract: Transmissible spongiform encephalopathies (TSE) or “prion diseases” have been related to the “protein‐only hypothesis”, which suggests that the “scrapie form (PrPSc)” of the prion protein (PrP) is the TSE infectious agent. The nmr structure of the ubiquitous benign cellular form of PrP (PrPC) consists of a globular domain of residues 126–231 with three α‐helices and a short β‐sheet, and a flexible extended “tail” of residues 23–125. The peptide segment of helix 1 has been implicated in various stages of hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 36 publications
5
43
1
Order By: Relevance
“…Although the double mutant H1[D147A,R151A] enhances conformational fluctuations it does not destabilize the helical structure entirely. In view of the high propensity of ␣-helix observed in the isolated H1 in conjunction with supporting experimental results (15)(16)(17), it is clear that alterations in the conformation of H1 are unlikely in the PrP C 3 PrP C * transition.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although the double mutant H1[D147A,R151A] enhances conformational fluctuations it does not destabilize the helical structure entirely. In view of the high propensity of ␣-helix observed in the isolated H1 in conjunction with supporting experimental results (15)(16)(17), it is clear that alterations in the conformation of H1 are unlikely in the PrP C 3 PrP C * transition.…”
Section: Discussionsupporting
confidence: 64%
“…Recent NMR experiments (8,14) showed that conformational fluctuations that originate in the C-terminal part of H2 are essential in the formation of PrP C *. Structural and mutational studies have shown that the relatively short helix 1 (H1) is stable over a range of pH values and solvent conditions, and hence is unlikely to undergo conformational change in the transition to PrP C * (15)(16)(17).…”
mentioning
confidence: 99%
“…A solution structure of a shorter mouse prion peptide mPrP (143-158), NDWEDRYYRENMYRYP, spanning helix H1 and 4 of 6 residues of loop L3, was previously published (59). It was shown that the residues involved in PrP C helix H1 also formed a helix in the peptide, whereas the loop region was less structured, suggesting no specific intramolecular interactions exist between these two peptide segments.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the highly dynamic nature of such peptides, which are in rapid conformational exchange of the helical conformation with unfolded conformers, no defined structure for the peptides can be determined. This restriction is also apparent from the analysis of 3 J(H a -H N ) coupling constants, which has been performed for the wild-type peptide (data not shown) and which shows similar trends as observed in other peptides, adding further support for highly dynamic helixcoil transitions [38]. Analysis of a-proton chemical shifts, however, provides a well-established measure of conformational preference and the population of helical states in such ensembles [45][46][47].…”
Section: Prp Helix 1 As a Test Casementioning
confidence: 99%
“…These investigation could prove by the analysis of circular dichroism as well as chemical shift data derived from NMR spectroscopy, that helix 1 retains its remarkable stability even as an isolated peptide in solution. [35,[37][38][39]. However, under aqueous buffer conditions, such peptides do not form rigid, well-defined structures, but rather dynamic, fluctuating ensembles, in which the helical conformer is in rapid conformational exchange with unfolded conformations.…”
Section: Prp Helix 1 As a Test Casementioning
confidence: 99%